Investigating the professional agency of English teachers in rural Ukrainian public schools - Park, Jean (2019)
The aim of this study is to understand how professional agency is constrained and enabled among English language teachers in public schools of a Ukrainian village. The data was obtained through focus group discussions, an interview, and written responses which included a total of sixteen Ukrainian English language teachers. Framed by the theory of the subject-centered sociocultural approach to teacher agency (Eteläpelto et al., 2013, p. 61), the study analyzed both the English language teachers as professional subjects and the sociocultural conditions in order to understand the manifestation of their professional agency. Findings show that the government, Ukrainian education program, the English language curriculum, and the school community are constraining factors of teacher agency; and the government, the school community and the English language teachers are enabling factors of teacher agency. This study provides an updated and comprehensive overview of the professional agency of teachers in Ukraine and can be used to further improve the English language curriculum.